Quality improvement in maternal and reproductive health services - Celia Karp; Erika M. Edwards; Hannah Tappis (BMC, 2024)
Abstract As maternal mortality and morbidity rates stagnate or increase worldwide, there is an urgent need to address health system issues that impede access to high-quality care. Learning from efforts to address the value, safety, and effectiveness of reproductive and maternal health care is essential to advancing quality improvement efforts.